2014
DOI: 10.1021/nn505632b
|View full text |Cite
|
Sign up to set email alerts
|

Wafer Scale Formation of Monocrystalline Silicon-Based Mie Resonators via Silicon-on-Insulator Dewetting

Abstract: Subwavelength-sized dielectric Mie resonators have recently emerged as a promising photonic platform, as they combine the advantages of dielectric microstructures and metallic nanoparticles supporting surface plasmon polaritons. Here, we report the capabilities of a dewetting-based process, independent of the sample size, to fabricate Si-based resonators over large scales starting from commercial silicon-on-insulator (SOI) substrates. Spontaneous dewetting is shown to allow the production of monocrystalline Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
121
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 97 publications
(132 citation statements)
references
References 48 publications
9
121
0
Order By: Relevance
“…All these properties can be modified by adding Ge before, during or after dewetting [42][43][44][45]60,61,63 potentially providing full control over their physical properties. However, in SiGe-based samples, Si-rich and Ge-rich particles are spatially separate, leading to large inhomogeneities of the morphological properties over micrometric distances 44,60,61 that make this method unsuitable for performing devices.…”
Section: A Solid State Dewetting For Sige-based Mie Resonatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…All these properties can be modified by adding Ge before, during or after dewetting [42][43][44][45]60,61,63 potentially providing full control over their physical properties. However, in SiGe-based samples, Si-rich and Ge-rich particles are spatially separate, leading to large inhomogeneities of the morphological properties over micrometric distances 44,60,61 that make this method unsuitable for performing devices.…”
Section: A Solid State Dewetting For Sige-based Mie Resonatorsmentioning
confidence: 99%
“…One viable and promising route is solid-state dewetting of ultra-thin films of metals 18,[34][35][36][37][38][39][40][41] and semiconductors, [42][43][44][45][46] a natural phenomenon exploited for the self-assembly of high-quality photonic structures. The instability giving rise to the dewetting phenomenon in thin films is mediated by the surface diffusion of atoms and occurs upon annealing at high temperature (even well below the melting point of the material) [47][48][49][50][51][52][53][54][55][56][57][58] .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, various methods of the resonant silicon nanoparticles fabrication have been developed during last years, including colloidal chemistry 23 , thin film dewetting 24 and laser ablation 6,25 , where initially crystalline samples or additional annealing were used to achieve crystalline state of the nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the structure of the dewetted layers can be controlled using several techniques such as pulsed laser annealing [35,36] or a substrate patterned by focused ion beam. The study of Ge dewetting on SiO 2 [37] has already been reported in the literature, however, only in the case of very thin amorphous Ge layers (5−15 nm thick) [38][39][40].…”
Section: Resultsmentioning
confidence: 99%